Principal Leadership in Increasing the Professionalism of Elementary School Teachers in Banyuasin Regency - Arwan Arwan; Abdul Hadi; Ade Akhmad Saputra (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the role of the principal's leadership in improving the professionalism of teachers at a public elementary school Banyuasin III. The data source of this research comes from the results of interviews with school principals and teachers. Methods such as interviews, participant observation, and documentation are used to gather data. Data reduction, visualisation, and verification are the data analysis strategies. He has stressed the need of instructors maintaining a professional demeanour at all times in his role as an educator. After preparing a plan, their role as managers is to urge teachers to teach the content in line with the current curriculum. In their role as administrators, they also make sure that teachers have everything they need to do their jobs well and that the school or institution meets its goals. Actively supervising teachers and providing direction and guidance is part of his or her job description as a supervisor. Working as a leader, I oversee teachers as they complete learning tasks and offer guidance on the subject matter to be taught. Improving the quality of teacher learning and encouraging teachers to employ information technology in learning are two of their goals as innovators. Encourage your students to work hard and do their best in class. Motivate and urge students to study more if you want them to succeed. In its role as an entrepreneur, it collaborates closely with the school committee and strives to think of innovative ways to empower teachers so that they can improve their professionalism in the classroom.